2021
DOI: 10.1212/wnl.0000000000011749
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Cognitive and Brain Changes in Korsakoff Syndrome

Abstract: ObjectiveTo investigate, in Korsakoff patients (KS), cognitive and brain changes over months and up to 10 years after the diagnosis.MethodsTwo groups of 8 KS patients underwent neuropsychological, motor and neuroimaging investigations including structural MRI and 18F-FDG-PET. The KSC group was examined early after the KS diagnosis (KSC-T1) and one year later (KSC-T2). The KSR group was evaluated 10 years after the diagnosis. Longitudinal comparisons in KSC explored short-term changes while cross-sectional comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…The ATN have reciprocal connections with at least three distinct memory structures, namely the medial prefrontal cortex (mPFC), retrosplenial cortex (RSC) and subicular regions of the hippocampal formation (HF) (Bubb et al, 2017;Mathiasen et al, 2017). The importance of the ATN for memory is supported by extensive clinical and experimental evidence (Aggleton, 2008;Aggleton et al, 2016;Barnett et al, 2021;Carlesimo et al, 2011;Dalrymple-Alford et al, 2015;Harding et al, 2000;Kim et al, 2009;Kopelman, 2015;Liu et al, 2021;Maillard et al, 2021;Sweeney-Reed et al, 2021;Wolff et al, 2015). This evidence is consistent with the perspective that the ATN are a critical hub that actively coordinates information processing among telencephalic memory structures (Wolff and Vann, 2019).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The ATN have reciprocal connections with at least three distinct memory structures, namely the medial prefrontal cortex (mPFC), retrosplenial cortex (RSC) and subicular regions of the hippocampal formation (HF) (Bubb et al, 2017;Mathiasen et al, 2017). The importance of the ATN for memory is supported by extensive clinical and experimental evidence (Aggleton, 2008;Aggleton et al, 2016;Barnett et al, 2021;Carlesimo et al, 2011;Dalrymple-Alford et al, 2015;Harding et al, 2000;Kim et al, 2009;Kopelman, 2015;Liu et al, 2021;Maillard et al, 2021;Sweeney-Reed et al, 2021;Wolff et al, 2015). This evidence is consistent with the perspective that the ATN are a critical hub that actively coordinates information processing among telencephalic memory structures (Wolff and Vann, 2019).…”
Section: Introductionsupporting
confidence: 54%
“…Extensive clinical and experimental evidence supports the conclusion that the anterior thalamic nuclei (ATN) make a significant contribution to memory function (Aggleton, 2008; Aggleton et al, 2016; Barnett et al, 2021; Carlesimo et al, 2011; Dalrymple-Alford et al, 2015; Harding et al, 2000; Kim et al, 2009; Kopelman, 2015; Liu et al, 2021; Maillard et al, 2021; Sweeney-Reed et al, 2021; Wolff et al, 2015). This influence is consistent with the ATN’s strong reciprocal connections with three distinct memory structures, namely the medial prefrontal cortex (mPFC), retrosplenial cortex (RSC) and the hippocampal formation (HF) (Aggleton et al, 2016; Bubb et al, 2017; Mathiasen et al, 2017; Nelson, 2021; Shibata, 1993a, 1993b; van Groen et al, 1999; van Groen and Wyss, 1990; van Groen and Wyss, 1995).…”
Section: Introductionmentioning
confidence: 92%
“…The pattern of connections suggests that this small brain region is a critical subcortical node that supports episodic memory. This perspective aligns with evidence that loss of ATN neurons in people with the Korsakoff’s syndrome, which is characterised by persistent and severe amnesia, discriminates these patients from alcoholic individuals who retain relatively good memory (Harding, Halliday, Caine, & Kril, 2000; Kopelman, 2015; Maillard et al, 2021). Intra-thalamic recordings in epilepsy patients also reinforce the association between ATN function and memory (Sweeney-Reed et al, 2021).…”
Section: Introductionsupporting
confidence: 79%
“…Among the few prospective data on the change of cognitive impairment in Wernicke-Korsakoff syndrome or severe ARCI, two studies deserve a specific attention (Fujiwara et al, 2008;Maillard et al, 2021). Regarding the episodic memory impairment, both Fujiwara et al (n = 20) and Maillard et al (n = 8) showed the stability of impairment (Fujiwara et al, 2008;Maillard et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Among the few prospective data on the change of cognitive impairment in Wernicke-Korsakoff syndrome or severe ARCI, two studies deserve a specific attention (Fujiwara et al, 2008;Maillard et al, 2021). Regarding the episodic memory impairment, both Fujiwara et al (n = 20) and Maillard et al (n = 8) showed the stability of impairment (Fujiwara et al, 2008;Maillard et al, 2021). Regarding the executive functions, the results were discordant and only Fujiwara et al showed a possible improvement in some of the executive functions at follow-up after 2 years, but the patients were abstinent since several years at baseline (Fujiwara et al, 2008).…”
Section: Introductionmentioning
confidence: 99%